L’université à l’ère de l’anthropocène : repenser l’éducation au politique par l’écologie - Christophe Point (Éducation et Socialisation)
This work invents a fictional dialogue between Hannah Arendt and Greta Thunberg on the topic of the place of political ecology in the university. The aim of this work consist of examining the theoretical framework necessary for the inclusion of political ecology education in the university. First, we focuse on the obstacles to the development of an authentic academic pedagogy on this subject. More specifically, we take the example of Hannah Arendt's philosophy to illustrate the conceptual dualisms between the child and the world, education and politics, education and instruction. In our opinion, these dualisms prevent us from thinking pedagogically and politically about the place of ecology within universities. Their damage is then illustrated by our understanding of eco-anxiety. Finally, we propose some prospective and general approaches to include ecology as an epistemological framework for university research, teaching and training.